THE INFLUENCE OF PROFITABILITY, ENVIRONMENTAL PERFORMANCE, COMPANY SIZE AND MEDIA EXPOSURE ON CARBON EMISSION DISCLOSURE IN LISTED BASIC INDUSTRY AND CHEMICAL SECTOR COMPANIES ON THE INDONESIA STOCK EXCHANGE IN 2021-2023 - Ema Marlini; Mursidah (RADJA PUBLIKA, 2025)
This study aims to examine the effect of profitability, environmental performance, firm size and media exposure on carbon emission disclosure in basic and chemical industry sector companies listed on the Indonesia Stock Exchange in 2021-2023. The population in this study amounted to 77 companies. The sampling technique used purposive sampling to obtain 25 company samples with 75 observations. This research is a quantitative research using secondary data collected using documentation and literature study techniques obtained through the official website of the Indonesia Stock Exchangewww.idx.co.idand the official website of each company which was processed with panel data regression analysis using EViews 12. The results showed that the variables profitability, firm size and media exposure did not affect carbon emission disclosure while the environmental performance variable had a positive and significant effect on carbon emission disclosure.